DDR and SSR in War-to-Peace Transition - von Dyck, Christopher (SSR Papers, 2016)
While disarmament, demobilization and reintegration (DDR) and security sector reform (SSR) have become integral statebuilding tools in post-conflict states, the existing empirical literature examining their relationship has focused on supply-side considerations related to the programming of both processes. In practice, though, DDR and SSR are implemented in the wider context of war-to-peace transitions where the state is attempting to establish a monopoly over the use of force and legitimize itself in the eyes of domestic and international communities. This paper therefore assumes that to identify opportunities and constraints for establishing closer practical linkages between DDR and SSR it is important to take the local politics into consideration. It examines two past externally driven peacebuilding interventions in West Africa, namely Liberia and Sierra Leone, featuring cases in which the central state had essentially fragmented or collapsed. Through this comparative analysis, the paper aims to provide a stepping-stone for future studies examining demand-side considerations of DDR and SSR in post-conflict contexts.